Rural poverty, agricultural production, and prices: a reexamination - Ahluwalia, Montek S. (International Food Policy Research Institute, 1985)
In his insghtfull but unfinished work, Dharm Narain drew attention to the behavior of prices as one of the important factors determining the extent of poverty in rural India. His empirical investigations, summarized in Gunvant Desai's contribution to this volume (chap. 1), provide strong prima facie evidence of such influence. Dharm Narain found that rural poverty is not only inversely related to the level of output per head of the rural population, as established in Ahluwalia (1978a), but also positively related to the level of prices.